2021
DOI: 10.3390/antiox10121960
|View full text |Cite
|
Sign up to set email alerts
|

Increased Kynurenine Indicates a Fatal Course of COVID-19

Abstract: (1) Background: An inefficient immune response accompanied by an overwhelming inflammatory reaction is involved in severe courses of COVID-19. Kynurenine (KYN) has important immune-modulatory functions and may contribute to a failure in controlling SARS-CoV-2. The present study aims to explore biomarkers that hint at a fatal outcome of COVID-19 early on. (2) Methods: We established a cohort of 148 hospitalized COVID-19 patients for this study. Thirty-one patients died due to a severe COVID-19 course, and 117 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 57 publications
(71 reference statements)
2
20
0
Order By: Relevance
“…Within the identified significantly different molecules in plasma (Figure 3A heatmap and Online Supplementary Table S2) tryptophan metabolites deserve consideration. As previously described (31), tryptophan metabolism is altered in COVID-19 plasma, resulting in decreased anthranilate and indole acetaldehyde and increased kynurenine in patients, which is associated with a higher mortality risk (31, 32) (Figure 3C). Compared to control conditions (CinC), plasma kynurenine significantly increases upon exposure of patient RBCs in control plasma (PinC).…”
Section: Resultssupporting
confidence: 70%
“…Within the identified significantly different molecules in plasma (Figure 3A heatmap and Online Supplementary Table S2) tryptophan metabolites deserve consideration. As previously described (31), tryptophan metabolism is altered in COVID-19 plasma, resulting in decreased anthranilate and indole acetaldehyde and increased kynurenine in patients, which is associated with a higher mortality risk (31, 32) (Figure 3C). Compared to control conditions (CinC), plasma kynurenine significantly increases upon exposure of patient RBCs in control plasma (PinC).…”
Section: Resultssupporting
confidence: 70%
“…While Mangge et al suggested KYN level as a potential marker in determining the fatality of COVID‐19 patients, fatality was not evaluated in our study. 27 Danlos et al, 28 on the contrary, suggested an inhibitory effect of KYN or anthranilic acid on IDO and TPO, having an immunosuppressive effect. Particularly, according to the results of correlation analysis in patient and total groups, KYN pathway metabolites (especially KYN:TRP ratio, PA, and QA) may be markers of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…5 In this study, significant correlations were found between N:L ratio, procalcitonin, CRP, IL-6, and ferritin and some KYN pathway metabolites, especially in the total and COVID-19 patient groups, but no significant correlations were found in the healthy group ( determining the fatality of COVID-19 patients, fatality was not evaluated in our study. 27 Danlos et al, 28 on the contrary, suggested an inhibitory effect of KYN or anthranilic acid on IDO and TPO, having an immunosuppressive effect. Particularly, according to the results of correlation analysis in patient and total groups, KYN pathway metabolites (especially KYN:TRP ratio, PA, and QA) may be markers of the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen full-text papers were eligible for the systematic review after 11 records were removed from the initial number of articles. Finally, the meta-analysis involved 14 articles as 5 papers were excluded for reasons listed in ESF, Table 3 (Blasco, Bessy et al 2020, Fraser, Slessarev et al 2020, Kimhofer, Lodge et al 2020, Robertson, Gostner et al 2020, Thomas, Stefanoni et al 2020, Ansone, Briviba et al 2021, D’Amora, Silva et al 2021, Herrera-Van Oostdam, Castaneda-Delgado et al 2021, Lawler, Gray et al 2021, Lionetto, Ulivieri et al 2021, Mangge, Herrmann et al 2021, Marin-Corral, Rodriguez-Morato et al 2021, Michaelis, Zelzer et al 2021, Xiao, Nie et al 2021).…”
Section: Resultsmentioning
confidence: 99%